Charakterystyka zagrożeń górniczych w polskim prawie – wybrane aspekty - Kołecki, Jakub Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego. Wydawnictwo "Szermierz" sp. z o.o., 2023)
Mining threats are a serious problem related to human mining activity. The problem of their occurrence has been extensively regulated by law and has been the subject of numerous court decisions. Due to the heterogeneity of threats, at the same time the methods of preventing them are characterized by a great variety. Steps that should be taken in accordance with the law, inter alia, by competent state authorities, entrepreneurs conducting mining activity or other specific entities legally related to the mining industry, often differ significantly. These differences are particularly visible in the context of the type of threats encountered in the course of carrying out this activity. In this article, the author wishes to analyze selected mining hazards in the light of Polish law regulations. This is to be achieved through the systematization of threats, which is intended to emphasize the common elements and the differences between them. The article is also intended to be a contribution to the next publication of the results of future research aimed at the description and exegesis of the most important police duties imposed on mining entrepreneurs in this field. They result to a large extent from the way in which the issues of mining hazards are regulated in Polish law.
Keywords: mining hazard; security; type of mining plant; type of minerals mined; mining entrepreneur